ARCHAEOLOGICAL HERITAGE OF PREHISTORIC CAVES IN BA THUOC DISTRICT, THANH HOA PROVINCE: PRESERVATION AND PROMOTION - Khac Su Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Ba Thuoc is a mountainous district in western Thanh Hoa Province, where more than 20 archaeological sites have been discovered. One of the outstanding features here is the presence of Middle Pleistocene fauna in Lang Trang cave, including fossils of Gigantopithecus blacki, a giant ape. The appearance of early modern human fossils in the Late Pleistocene proves that Vietnam was the site of the earliest modern human evolution in Southeast Asia. In Ba Thuoc district, human communities were in continuous residence from 30,000 to 7,000 years BP and developed the Dieu stone craft industry. This industry merged with the Hoabinhian industry in the development process, creating a cultural nuance for the land of Ba Thuoc. By 7,000 years BP, the boundary between the two industries was virtually nonexistent. The prehistoric inhabitants here contributed to the formation of Middle Neolithic cultures in North Central Vietnam. In addition, the caves in Ba Thuoc were also places for the mountain-dwelling inhabitants of the Dong Son culture to visit and bury their dead in the centuries before and after the beginning of the common era. In this study, we systematized the documents on monuments and artifacts, and evaluated the outstanding cultural heritage of the prehistoric caves in Ba Thuoc district, which need to be preserved and promoted in the present day.